Characterization of a visual environment to support SCRUM ceremonies - Ribeiro, Pedro Abreu (2019)
Agile software development methodologies, such as Scrum, have been widely used today because they offer great benefits to their users, such as accelerating processes and resources to deal with instability in technological environments. The Scrum methodology focuses on the management and organization of software projects but does not provide detailed descriptions of how everything should be done in a project. Rapid customer feedback and support for volatile requirements result in a higher product value, however, initial requirement analysis using modeling techniques is not commonly used in agile processes such as Scrum to prepare the implementation phase of the project. This article is intended to briefly describe the approach proposed to support Sprint and Product Backlog using Unified Modeling Language (UML), based modeling techniques.